COOPERATIVE INTEGRATED READING AND COMPOSITION SEBAGAI PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN KEMAMPUAN MENEMUKAN IDE POKOK DI SDN 46 BANDA ACEH - Anggi Desky; Silvia Sandi Wisuda Lubis (Al-Azkiya: Jurnal Pendidikan MI/SD, 2026)
This study aims to improve the ability of third-grade students at SDN 46 Banda Aceh to identify the main ideas of reading texts through the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, consisting of four stages: planning, acting, observing, and reflecting. The subjects were 29 third-grade students, including 19 boys and 10 girls. Data were collected through observation of student activities and group performance in determining main ideas from reading passages. The findings show a significant improvement in students’ ability to identify main ideas after the application of the learning model. In the pre-cycle stage, the average group score was 61.3, categorized as sufficient. After the implementation of Cycle I, the average score increased to 75.0, categorized as good. In Cycle II, the average score further increased to 87.2, categorized as very good. All groups surpassed the minimum mastery criteria, indicating that this model is effective in helping students understand paragraph structure and enhance reading comprehension through collaborative activities. Based on these results, it can be concluded that the implementation of the CIRC model is effective in improving students’ ability to identify main ideas while also promoting cooperation and active participation in Indonesian language learning.